Comparative effectiveness of routine physical therapy with and without instrument assisted soft tissue mobilization in patients with neck pain due to upper crossed syndrome - Tahir Mahmood; Waqar Afzal; Umair Ahmad; Muhammad Asim Arif; Ashfaq Ahmad (Journal of the Pakistan Medical Association, 2021)
Objective: To determine the effectiveness of routine physical therapy with and without Instrument Assisted soft Tissue Mobilization on pain intensity, range of motion in patients with neck pain due to upper crossed syndrome. Methods: It was Randomized clinical trial. The data was collected from Physiotherapy Clinics, The Agile Institute of rehabilitation Sciences (AIRS) and National Orthopedic Hospital Bahawalpur. The study was completed from 28 August 2019 to29 February 2020 after the approval .60 patients of upper crossed syndrome diagnosed patients complaining neck pain with forwarded head posture in age range of 18-40 years were included based on following Inclusion and exclusion criteria. The subjects were divided into two equal groups of 30 each using non-probability purposive sampling technique. Outcome tool used were Inclinometer to assess range of motion and Pain by Numeric pain Rating Scale. The Data was analysed by using SPSS version 22. Criteria of significance i.e. p-value<0.05 was taken as significant at 95% Confidence Interval. Results: Pain rating at base line in experimental compared to routine physical therapy show significant improvement as P value was 0.01.The results of Neck Flexion P=0.03, Neck Right Bending P=.00, Neck Left Bending P=0.00. The results for Neck extension 0.25 show that both techniques were equally effective. Conclusion: The study concluded that addition that Instrument soft tissue mobilization with combination of stretching exercise is more effective in management of symptoms of upper crossed syndrome. Clinical Trial Number: [IRCT20190912044754N1] Keywords: IASTM, Neck Pain, Upper Crossed Syndrome, Neck Range of Motion Continuous...